Cell Fusion Overviews and Methods - Pfannkuche, Kurt.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume details protocols on detection and analysis of fusion events in various cell types in vitro and in vivo. Additional, protocols aim to facilitate the future highly relevant process of engineering cells for specific purposes, such as generation of transgenic embryos and development of hybrid cells, in order to tackle specific tasks in cell biology and medicine. Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Practical and authoritative, Cell Fusion: Overviews and Methods, Second Edition serves as an ideal reference on cell fusion and laboratory protocols.
State of the Art in Cell-Cell Fusion -- Fusion in Cancer: An Explanatory Model for Aneuploidy, Metastasis Formatio, and Drug Resistance -- Mouse Embryos´ Fusion for the Tetraploid Complementation Assay -- Generation of Mouse Chimeras with High Contribution of Tetraploid Embryonic Stem Cells and Embryonic Stem Cell-fibroblast Hybrid Cells -- Microfluidic Systems for Cell Pairing and Fusion -- Chromosome Tracking in Fused Cells by Single Nucleotide Polymorphisms -- Fusion of Mesenchymal Stem Cells and Islet Cells for Cell Therapy -- Detection of Fusion Events in Mammalian Skeletal Muscle -- FISH Detection of X and Y Chromosomes in Combination with Immunofluorescence to Study Contribution of Transplanted Cells to Skeletal Muscle Fibers -- Using Phosphatidylserine Exposure on Apoptotic Cells to Stimulate Myoblast Fusion -- Tracing Myoblast Fusion in Drosophila Embryos by Fluorescent Actin Probes -- Analysing Cell Fusion Events Within the Central Nervous System using Bone Marrow Chimerism -- Cell Fusion Between Dendritic Cells and Whole Tumor Cells -- Membrane Nanotube Formation in Osteoclastogenesis -- Modified Adherence Method (MAM) for Electrofusion of Anchorage Dependent Cells -- FRET in the Analysis of in vitro Cell-cell Fusion by Flow Cytometry -- Dual Split Protein (DSP) Assay to Monitor Cell-cell Membrane Fusion -- Photoconvertible Fluorescent Protein‐based Live Imaging of Mitochondrial Fusion.
Keywords: Cell biology; Cell Biology